THE EFFECTIVENESS OF THE LUMBOPELVIC STABILIZATION EXERCISE WITH RHYTMIC STABILIZATION ON MICROWAVE DIATHERMY INTERVENTIONS TO REDUCE DISABILITY DUE TO MYOGENIC LOW BACK PAIN - Widnyana, Made; Winaya, I Made Niko; Prabawa, Made Yoga; Putra, I Putu Yudi Pramana; Utama, Anak Agung Gede Eka Septian (Sport and Fitness Journal; Vol 9 No 3 (2021): Volume 9, No. 3, September 2021DO - 10.24843/spj.2021.v09.i03.p06, 2021)
Myogenic low back pain (LBP) is pain that caused by myogenic (muscle) factors as a source of pain. Myogenic LBP can cause disability in patients. The aim of this study was to compare the effectiveness of lumbopelvic stabilization exercise and microwave diathermy with rhythmic stabilization exercise and microwave diathermy in reducing disability due to myogenic LBP. The research method was experimental research with pre-test and post-test two group design. There were two groups randomly selected by the block permutation technique. The first group consisted of 16 samples who received lumbopelvic stabilization exercise and microwave diathermy treatment, while the second group consisted of 16 samples who received rhythmic stabilization and microwave diathermy treatment. Disability is measured by using the MODI (Modified Oswestry Disability Index) questionnaire. The study was conducted at a physiotherapy clinic in Denpasar. The results of the study after the Paired T-Test were carried out in each group with a p value <0.05, this indicated that there was a significant difference between the pre-test and post-test results in each group. The difference test between groups was carried out with the Independent T-Test, getting a p value <0.05, this indicates that there is a significant difference between the first group and the second group. The conclusion of this study is that lumbopelvic stabilization exercise and micreowave diathermy reduce disability better than rhythmic stabilization and microwave diathermy due to myogenic lower back pain. Keywords : Disability, lumbopelvic stabilization exercise, myogenic lower back pain, rhythmic stabilization